Oral Lactoferrin to Prevent Nosocomial Sepsis and Necrotizing Enterocolitis of Premature Neonates and Effect on T-Regulatory Cells - Akin, Ilke Mungan; Atasay, Begum; Dogu, Figen; Okulu, Emel; Arsan, Saadet; Karatas, H. Deniz; Ikinciogullari, Aydan; Turmen, Tomris (American Journal of Perinatology, 2014)
Objective Lactoferrin (LF) is effective in the prevention of sepsis in very low birth weight (VLBW) neonates. T-regulatory cells (Tregs) are important subsets of T lymphocytes that control pathogen-specific immune responses and are essential for intestinal immune homoeostasis. The aim of the present study is to determine whether oral LF at a dosage of 200 mg/d reduces nosocomial sepsis episodes and necrotizing enterocolitis (NEC) in premature infants and to evaluate the possible effects of LF on Treg levels.Study Design In this prospective, placebo-controlled, double-blind, randomized trial, infants either VLBW or born before 32 weeks were assigned to receive either placebo (n = 25), or 200 mg LF (n = 25) daily throughout hospitalization. Episodes of culture proven nosocomial sepsis and NEC were recorded. The level of FOXP3 + CD4 + CD25hi lymphocytes was studied by flow cytometry at birth and discharge. A third comparison was made with healthy term neonates (n = 16).Results Fewer sepsis episodes were observed in LF-treated infants (4.4 vs. 17.3/1,000 patient days, p = 0.007) with none developing NEC, without statistical significance. Treg levels at birth and discharge were similar, while preterm infants showed significantly lower levels than term controls. However, individual increases in Treg levels were higher in the LF group.Conclusion LF prophylaxis reduced nosocomial sepsis episodes. Treg levels in preterm infants were lower than in term infants and an increase of Treg levels under LF prophylaxis was observed. Increase in Treg levels can be the mechanism for protective effects of LF on nosocomial sepsis.
Keywords: lactoferrin; VLBW; sepsis; NEC; T-regulatory lymphocytes